2019
DOI: 10.1093/tas/txz114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ractopamine hydrochloride supplementation on feeding behavior, growth performance, and carcass characteristics of finishing steers1,2

Abstract: Ractopamine hydrochloride (RAC) is a β-adrenergic agonist that functions as a repartitioning agent to improve muscling in feedlot cattle. Many studies have investigated the effects of RAC on growth performance and carcass characteristics; however, there is minimal information about the influence of RAC on feeding behavior. Sixty-nine steers (body weight [BW] = 364 ± 3.9 kg) predominately of Angus and Simmental breeding were subjected to a 126-d (n = 46) or 154-d (n = 23) feeding period and randomly assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Supplementation with RH did not improve the HCW or LM area of the BA treatment compared to IMP but resulted in advanced carcass maturity. Others have reported no difference in HCW ( Quinn et al, 2008 ; Strydom et al, 2009 ; Hales et al, 2016 ; Hunter-Beasley, et al, 2018 ; Trotta et al, 2019 ) or LM area ( Walker et al, 2006 ; Quinn et al, 2008 ; Strydom et al, 2009 ; Hales et al, 2016 ; Hunter-Beasley, et al, 2018 ) of RH supplemented cattle compared with non-supplemented controls. However, it is unclear why the LM area of BA was 4.6 cm 2 smaller than IMP in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Supplementation with RH did not improve the HCW or LM area of the BA treatment compared to IMP but resulted in advanced carcass maturity. Others have reported no difference in HCW ( Quinn et al, 2008 ; Strydom et al, 2009 ; Hales et al, 2016 ; Hunter-Beasley, et al, 2018 ; Trotta et al, 2019 ) or LM area ( Walker et al, 2006 ; Quinn et al, 2008 ; Strydom et al, 2009 ; Hales et al, 2016 ; Hunter-Beasley, et al, 2018 ) of RH supplemented cattle compared with non-supplemented controls. However, it is unclear why the LM area of BA was 4.6 cm 2 smaller than IMP in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Ractopamine is also used to favor the FCR in the livestock industry ( Hales et al 2016 ). Besides, Ronald et al (2019 ) reported that ractopamine could induce a significant rise in weight gain and improve FCR. Likely, Abd-elfattah et al (2019 ) stated that vaccination with the RHD virus vaccine did not significantly affect body weight and FCR.…”
Section: Discussionmentioning
confidence: 99%
“…Beta-agonists effectively stimulate cattle growth ( Kootstra et al , 2005 ). It is used to enhance physical performance ( Ronald et al , 2019 ). According to Mirhendi et al (2014 ), beta-adrenergic agonists enhance the growth performance of chicken.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, when supplemented with RAC at 300 mg/d for 28 d, steers had a greater number of daily feeding events and those events were in shorter duration [ 44 ]. In contrast, when feeding RAC over a longer 42 d period, visit eating time, per meal, and per day were reduced in steers [ 45 ]. Further, when RAC was supplemented at 200 mg/d for 30 d, steers had an extended time required to consume daily feed [ 33 ].…”
Section: Discussionmentioning
confidence: 99%